2016
DOI: 10.7322/jhgd.110985
|View full text |Cite
|
Sign up to set email alerts
|

Health of sexual minorities in north-eastern Brazil: representations, behaviours and obstacles

Abstract: Objective: The aim of this study was to identify the social representations (SR) of health and major inequities, obstacles and challenges experienced by lesbians, gays, bisexuals, and transgenders regarding access to health services. Methods: This qualitative research was conducted with a group of sexual minorities recruited using the snowball technique. The data were organised according to Bardin and analysed from the perspective of SR. Results: Twelve gays, nine transvestites, six lesbians and three bisexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
1
5
0
12
Order By: Relevance
“…Although most participants in this study were heterosexual, which can be justified by the stimulus to early sexuality and the possibility of paid sex (26) , homosexuals are the ones who are strongly stigmatized and linked to large manifestations of exclusion and blamed for HIV infection (22,27) ; this is similar to what happens with drug users, being labelled and socially excluded (6,18,22,27) . We found that interruption of ART was not predominant in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Although most participants in this study were heterosexual, which can be justified by the stimulus to early sexuality and the possibility of paid sex (26) , homosexuals are the ones who are strongly stigmatized and linked to large manifestations of exclusion and blamed for HIV infection (22,27) ; this is similar to what happens with drug users, being labelled and socially excluded (6,18,22,27) . We found that interruption of ART was not predominant in this study.…”
Section: Discussionmentioning
confidence: 79%
“…(Velho et al, 2010). Salienta-se que o sexo anal quando realizado sem o preservativo pode ser um risco para infecção pelo HIV, como foi demonstrado em estudo que 79% dos homens haviam mantido relações sexuais anais desprotegidos (Garcia, Albuquerque, Drezett, & Adami, 2016), tendo em vista que o sexo anal sem o uso do preservativo o risco de transmissão de DST/HIV é cinco vezes maior, pois o ânus durante a penetração na atividade sexual pode sofrer lesões (Nicolau et al, 2012).…”
Section: Discussionunclassified
“…A temática da população transgênera com as IST e a AIDS são abordadas nos quatro artigos (Ferreira, Pedrosa, & Nascimento, 2018;Garcia, Albuquerque, & Adami, 2016;Rocon, Rodrigues, Zamboni, & Pedrini, 2016;Souza & Pereira, 2015). Segundo Calderaro et al (2008) Calderaro et al (2008) apontaram que a saúde da população transgênera não pode ser restrita ao campo da IST/AIDS, pois, segundo os autores, todas as doenças físicas e psíquicas podem atingir a população como um todo, além de que ao buscarem cuidados de saúde se depararem com situações que não ocorreriam na vida de quem está inserido no binarismo heteronormativo.…”
Section: Categoria 3 -Ist/aidsunclassified